2015
DOI: 10.5194/isprsarchives-xl-7-w3-77-2015
|View full text |Cite
|
Sign up to set email alerts
|

Rice-planted area extraction by time series analysis of ENVISAT ASAR WS data using a phenology-based classification approach: A case study for Red River Delta, Vietnam

Abstract: ABSTRACT:Recent studies have shown the potential of Synthetic Aperture Radars (SAR) for mapping of rice fields and some other vegetation types. For rice field classification, conventional classification techniques have been mostly used including manual threshold-based and supervised classification approaches. The challenge of the threshold-based approach is to find acceptable thresholds to be used for each individual SAR scene. Furthermore, the influence of local incidence angle on backscatter hinders using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…The main Remote Sens. 2016, 8, 279 5 of 28 distinctive feature between locations with a single, exclusively rainfed crop and multi-cropped areas with at least one irrigated cycle is therefore the occurrence of a winter and/or spring crop [58].…”
Section: Land Use/land Covermentioning
confidence: 99%
See 2 more Smart Citations
“…The main Remote Sens. 2016, 8, 279 5 of 28 distinctive feature between locations with a single, exclusively rainfed crop and multi-cropped areas with at least one irrigated cycle is therefore the occurrence of a winter and/or spring crop [58].…”
Section: Land Use/land Covermentioning
confidence: 99%
“…Literature sources report irrigated acreages varying from 670,000 to 850,000 ha, although the exact spatial and temporal scope of these figures is not always specified in these studies [43,45,[61][62][63]. These values are all somewhat lower than the acreage found in a recent Advanced Synthetic Aperture Radar (ASAR)-based study, reporting 1,180,000 ha of doublecropped rice for 2007-2011 [58], so some uncertainty persists. Overall, the new LULC map corresponds well with the majority of available information from other sources and suffices for the current purpose.…”
Section: Land Use/land Covermentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of our study is therefore to classify rice areas and determine the seasonality of rice crops in the Mekong Delta by using phenological techniques applied on multi-year Envisat ASAR WSM time series from 2007 to 2011. This study builds upon methods initially developed by Nguyen et al [60] over the Red River Delta, Vietnam.…”
mentioning
confidence: 99%
“…Due to the high frequent cloud cover in this area, Chuc et al proposed a compositing method for Landsat-8 images, which is used for rice mapping with XGBoost classifier later [29]. Other studies utilized time-series SAR imagery for rice classification using ML techniques including SVM [30,31], Simple Linear Iterative Clustering super-pixel algorithm [32], decision tree based on phenology analysis and the thresholding approach [33]. We found that the rice map of all 11 provinces in the RRD area has not been noticed due to the confusion in available administrative maps in previous studies.…”
Section: Monitoring Rice and Flooding Using Satellite Imagesmentioning
confidence: 99%